2008
DOI: 10.1029/2007jd009151
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial characteristics of positive and negative Indian Ocean dipole with and without ENSO

Abstract: [1] The differences in the temporal evolution and spatial characteristics of the Indian Ocean Dipole (IOD) between positive and negative events with and without ENSO have been investigated using observations for the period . To document such differences is particularly important for climate forecasts over far east Asia, since distinctly different monsoon activities over China, Korea, and Japan for different types of IOD are found in the composite maps of precipitation anomalies. The composite map of SST and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 43 publications
4
109
0
Order By: Relevance
“…In a personal communication related to the present paper, Field pointed out Hong et al (2008) reported that for the period of 1948-2002 that the strongest negative precipitation anomalies in the MC for June, July, August have occurred during periods of combined positive ENSO and IOD indices. In his own personal communication with Hong (2011), Field reported that the same was true for September, October, and November.…”
Section: Indian Ocean Dipolementioning
confidence: 99%
“…In a personal communication related to the present paper, Field pointed out Hong et al (2008) reported that for the period of 1948-2002 that the strongest negative precipitation anomalies in the MC for June, July, August have occurred during periods of combined positive ENSO and IOD indices. In his own personal communication with Hong (2011), Field reported that the same was true for September, October, and November.…”
Section: Indian Ocean Dipolementioning
confidence: 99%
“…Hong et al (2008) demonstrate that positive events (positive IOD, El Niño, and both combined) reduce the moisture inflow from the southerly moisture origins (Arabian Sea, Bay of Bengal, southeast monsoon) to the Tibetan plateau while these are strengthened during negative episodes (negative IOD, La Niña, and both combined).…”
mentioning
confidence: 99%
“…al., 2003;Krishnan and Swapna, 2009;Clark et al, 2000;Terray et al, 2003Terray et al, , 2007Yang et al, 2007;Izumo et al, 2008;Park et al, 2010;Boschat et al, 2010). Although Sea Surface Temperature (SST) anomalies over the equatorial IO are not statistically associated with ISM rainfall (Gadgil et al, 2004(Gadgil et al, , 2005(Gadgil et al, , 2007Ihara et al, 2007), a lot of attention has been paid to the Indian Ocean Dipole (IOD) over the years, with debate regarding its existence as an intrinsic mode of IO variability, its dependence with ENSO (Chang et al, 2006), as well as its relationship with ISM (Ashok et al, 2001(Ashok et al, , 2004Gadgil et al, 2004Gadgil et al, , 2005Gadgil et al, , 2007Loschnigg et al, 2003;Kulkarni et al, 2007;Drbohlav et al, 2007;Hong et al, 2008). However, even the most recent studies have obtained quite contradictory results on this subject.…”
Section: Introductionmentioning
confidence: 99%